PENGARUH PERANAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SMKN 5 BATAM - Serlyna Afriani; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Learning motivation is the encouragement, strength, or driving force that arises in a student to carry out an activity called learning. The teacher is one of the factors that influence motivation which impacts on student learning outcomes. So that there needs to be special attention to the motivation of students, especially a teacher must understand the learning motivation of students and there must be a follow up from the teacher if the students have low motivation to learn. The purpose of this study was to determine how the role of teachers in improving student motivation in SMK Negeri 5 Batam, to find out how student motivation is at SMK Negeri 5 Batam, find out how the influence of the role of teachers in improving motivation to learn in students at SMK Negeri 5 Batam. The subjects in this study were all students of SMK Negeri 5 Batam, totaling 1,988 people. The sample in this study was taken using proportional sampling technique with 10% of subjects from 1988 students, 198. Data were collected using observations, questionnaires, interviews, and documentation. In analyzing data using quantitative descriptive techniques with statistical tests. The results of this study indicate that the teacher's role in increasing student motivation is in the very good category. Student motivation in SMK Negeri 5 Batam is in the very good category. There is a significant influence in this study, this is evidenced by the results of a simple linear regression test between variables X and Y, obtained Fcount 28.464 and Ftable 3.89 shows that Fcount> Ftable, so that Ho is rejected and Ha is accepted. But the influence exerted was low, amounting to 0.356 with a percentage of 35.6%.Key Words: Influence, Teacher Role, Learning Motivation